Role of Intravenous Levetiracetam in Seizure Prophylaxis of Severe Traumatic Brain Injury Patients - KIRMANI, BATOOL F.; Mungall, Diana; Ling, Geoffrey (Frontiers in Neurology, 2013)
Traumatic brain injury (TBI) can cause seizures and the development of epilepsy. The incidence of seizures varies from 21% in patients with severe brain injuries to 50% in patients with war-related penetrating TBI. In the acute and sub-acute periods following injury, seizures can lead to increased intracranial pressure and cerebral edema, further complicating TBI management. Anticonvulsants should be used for seizure prophylaxis and treatment. Phenytoin is the most widely prescribed anticonvulsant in these patients. Intravenous levetiracetam, made available in 2006, is now being considered as an alternative to phenytoin in acute care settings. When compared with phenytoin, levetiracetam has fewer side-effects and drug-drug interactions. In the following, the role of levetiracetam in TBI care and the supporting evidence is discussed.